Manajemen Pendidikan untuk Meningkatkan Mutu Pendidikan Anak pada Guru Yayasan Al Mukhlisin - Endang Susilo Wardani; Ifa Nurmasari; Hamdi Supriadi (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
A large population is an asset for a nation in improving its quality of life. However, the rate of population growth that is not matched by an increase in quality can cause problems in the future. With regard to improving human resources, one of the parties who play an important role is the teacher. So that teachers can provide teaching in accordance with the development of the era that is developing rapidly as it is today, one of the solutions offered is to provide materials, motivation and experience to the teachers of the Al Mukhlisin Peduli Ummah Foundation. The method used in this Community Service is to provide knowledge, share experiences and provide motivation on how to improve the quality of teachers so that they can adapt to the rapid development of the times. So that what is taught by the teacher is more interesting and can improve the quality of the students he teaches. This activity is carried out while still complying with the Health protocol. The results of this Community Service activity show an increase in the knowledge, insight, motivation and experience of the teachers of the Al Mukhlisin Pndok Petir Depok Foundation. And will hold further cooperation in the field of Education to improve the quality of human resources.